Parameterization of a single H-bond in Orange Carotenoid Protein by atomic mutation reveals principles of evolutionary design of complex chemical photosystems - Moldenhauer, Marcus; Tseng, Hsueh-Wei; Kraskov, Anastasia; Tavraz, Neslihan N.; Yaroshevich, Igor A.; Hildebrandt, Peter; Sluchanko, Nikolai N.; Hochberg, Georg A.; Essen, Lars-Oliver; Budisa, Nediljko; Korf, Lukas; Maksimov, Eugene G.; et al. (Frontiers in Molecular Biosciences, 2023)
Dissecting the intricate networks of covalent and non-covalent interactions that stabilize complex protein structures is notoriously difficult and requires subtle atomic-level exchanges to precisely affect local chemical functionality. The function of the Orange Carotenoid Protein (OCP), a light-driven photoswitch involved in cyanobacterial photoprotection, depends strongly on two H-bonds between the 4-ketolated xanthophyll cofactor and two highly conserved residues in the C-terminal domain (Trp288 and Tyr201). By orthogonal translation, we replaced Trp288 in Synechocystis OCP with 3-benzothienyl-L-alanine (BTA), thereby exchanging the exocyclic imino nitrogen for a sulphur atom. Although the high-resolution (1.8 Å) crystal structure of the fully photoactive OCP-W288_BTA protein showed perfect isomorphism to the native structure, the spectroscopic and kinetic properties changed distinctly. We accurately parameterized the effects of the absence of a single H-bond on the spectroscopic and thermodynamic properties of OCP photoconversion and reveal general principles underlying the design of photoreceptors by natural evolution. Such "molecular surgery" is superior over trial-and-error methods in hypothesis-driven research of complex chemical systems.